Evaluation of the treatment of purified wastewater in the city of Bouira (Algeria) - Naziha, Lamri; Bachouche, Nassima; Bentaleb, Leila (Technium Social Sciences Journal, 2022)
Wastewater reuse is a popular practice in some regions of the world, affected by water shortages. After purification techniques, wastewater can be used in several areas of irrigation and industry. Only, there are international standards declared by the World Health Organization for these waters discharged from the sewage plant. In this research, we tried to evaluate these purified wastewaters by choosing the wastewater treatment plant of Bouira. We took samples of raw water and purified water to perform common physico-chemical analyses such as (pH, turbidity, temperature, BOD5, and conductivity), whose purpose is to control the quality of water before and after treatment. This control operation lasted one month (February and March) of the year 2022. The results of the physico-chemical parameters of raw wastewater and treated wastewater are analyzed and compared with the thresholds set by the wastewater treatment plant of Bouira. At the end, we have shown that the treated water does not practically meet the standards of discharge, because the values of the physico-chemical parameters and the parameters of pollution exceed the standards, which does not encourage their reuse.